Cognitive dissonance and its relationship to self-regulation among university students - Muhammad Hamid Muhammad , Researcher; م.د علي ربيع حسين , م; شيماء عامر عبيد إبراهيم , م.م; محمد ماجد طه , م. (lark, 2023)
The current research aims to identify cognitive dissonance and its relationship to self-regulation among university students, where the researchers relied in their research steps on the correlative descriptive approach, and chose the sample in a stratified random manner with (150) individuals (65) for males and (85) for females, and for each of the Department of Quranic Sciences And the Arabic language in the College of Education - Al-Qaim / University of Anbar, for all stages and for morning studies only, for the academic year 2021-2022. Results:1- There is no cognitive dissonance among the sample members.2- There are differences in cognitive dissonance according to the gender variable and in favor of males.3- As for self-regulation, the results were statistically significant among the sample members in general.4- There are no significant differences in self-organization according to the gender variable.5- The correlation between the two variables was positive and inversely negative.Based on these results, the researchers developed a set of recommendations and suggestions
Keywords: cognitive dissonance, self-regulation, university students